Dynamical Models of Axially Moving Rods with Tensile and Bending Stiffness. Issue 1 (2015) - Steinboeck, A.; Baumgart, M.; Stadler, G.; Saxinger, M.; Kugi, A.
Abstract: Many rods exhibit a coupling effect between axial and transversal displacements. Additional forces may be caused by a superimposed axial motion of the rod. We explore how these effects can be mathematically modeled using a rod with two local degrees of freedom. The resulting geometrically nonlinear model can be reduced to a system with just one local degree of freedom, i.e., the transverse displacement. These models are compared to commonly used modeling strategies where the rod is given just one local degree of freedom right at the beginning. Results from a numerical example complement the theoretical findings.